Warfarin Poisoning and Blunt Abdominal Trauma: A Rare Cause of Small Bowel Obstruction - Yeo, Jane H (Cureus, 2021)
Intestinal intramural hematomas are a rare complication of blunt abdominal trauma in the setting of anticoagulation. A 52-year-old male presented to our surgical service with high-grade small bowel obstruction secondary to an extensive small bowel intramural hematoma requiring resection. The patient sustained a blunt abdominal assault several days earlier and workup revealed severe coagulopathy likely secondary to overexposure to a warfarin-based substance. Few cases have been reported on coagulopathic traumatic small bowel hematomas causing small bowel obstruction. Current literature suggests non-operative management can be used safely; however, operative intervention is warranted if there are signs of ischemia or perforation. This case highlights the importance of a high index of suspicion, thorough investigation, and prompt intervention to avoid significant morbidity in small bowel obstruction secondary to intramural traumatic hematoma.